It Only Takes Everything You've Got!: Lessons for a Life of Success - Melara, Julio (London The Catalyst Group, 1998)
In "It Only Takes Everything You've Got!", Julio Melara offers personal strategies for living a life of success. Whether in business, home, sports or the classroom, you'll learn how to develop and practice the skills you need to reach your potential. After reading this book, you'll understand how meaningful success is and how it's within the grasp of anyone who chooses to reach it!
Includes Notes.
Keywords: Success